ОЦІНКА РЕЗУЛЬТАТІВ НАУКОВОЇ ДІЯЛЬНОСТІ В КЛАСИЧНИХ УНІВЕРСИТЕТАХ ПІДПРИЄМНИЦЬКОГО ТИПУ В УМОВАХ ЄВРОІНТЕГРАЦІЇ - A. Starostina; V. Osetskyi; V. Kravchenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)

(untitled)
The urgency of the research is driven by the need to select and apply such scientometric tools to estimate scientific and academic productivity of scholars from classical universities that are relevant to current economic environment in Ukraine and the entrepreneurial university model. The main approach to this research is based on systemic analysis of the modern scientific thought condition against estimation of scholars productivity; comparative analysis of scientometric Scopus, Web of Science and Google Scholar bases; determination of efficiency from applying commercial and free scientometric bases under entrepreneurial university model. This article aims at detecting an opportunity and viability of applying Google Scholar free scientometric base to estimate scholars productivity at classical universities in the context of Ukrainian environment. Based on the research results obtained, the hypothesis on association between h-index in Scopus and Google Scholar values for scholars of STEM and natural disciplines from classical universities has been proved. In addition, this article provides theoretical facts that evidence another hypothesis on an opportunity to design the so called h-index in ProxyScopus for scholars of socio-economic and humanitarian disciplines from classical universities. This approach allows improving efficiency of budget allocation for universities as well as productivity of the scholars, but also meets principles of entrepreneurial university framework. The article materials can be of great interest for management of classical universities, state education agencies on education and science as well as scholars and experts in the field of management of entrepreneurial universities.